Comparison of Different Foam Rolling Protocols on Ankle Range of Motion, Strength, Muscle Activation and Jump Performance - Enrico Soares; Vinícius Martins Almeida; Christine Megumi Wakuda de Abreu Vasconcelos; João Henrique Barbosa de Jesus; Charles Ricardo Lopes (International Journal of Strength and Conditioning, 2022)
Background: Foam rolling (FR) has been widely used with the intent to increase range of motion (ROM) before strength and power activities. At the moment, few studies have investigated practical strategies to control FR intensity. Purpose: The aim was to compare the effect (FR) intensity by different combinations of a smooth roller, grid roller, unilateral or bilateral rolling massage on the triceps suralis ROM, strength, muscle activation, and jump performance. Methods: Ten male (28±4 years, 175±5 cm, 81±13 kg) and ten female (29±4 years, 163±5 cm, 66±10 kg) recreationally trained performed two sessions of data collection that compared 4 combinations of rolling surface and technique: unilateral smooth roller (US), bilateral smooth roller (BS), unilateral grid roller (UG), and bilateral grid roller (BG). During all conditions, the triceps suralis was rolled for 2 sets of 60 s with 60 s of rest between sets. Rate of perceived pain (RPP) after the rolling protocol; peak force during a maximal voluntary isometric contraction (MVIC) (PF), muscle activation during a MVIC, and unilateral drop jump (UDJ) performance were measured before and after each condition. Results: The greatest RPP was reported in UG condition and the lowest RPP was reported in BS condition. All conditions increased ankle ROM to the same extent without subsequent effect on PF, muscle activity UDJ height, and UDJ contact time. Our data indicate that FR using different combinations of surface pattern and rolling techniques increased ankle ROM without a subsequent effect on drop jump performance, triceps suralis strength, and activation. Conclusion: In conclusion, practitioners could be encouraged to perform FR with mild discomfort and use a bilateral technique to save time.